FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN VOLUME TRANSAKSI SAHAM - Virginia, Chyntia Augustia; Lesmana, Iwan; Rumondang, Safrida (Indonesian Journal of Accounting and Governance, 2022)
This research aims to analyze factors that affect the growth in share transaction volume. Thevariables in this study are share price growth, earning per share (EPS), return on equity (ROE), anddebt to equity ratio (DER). The sample used in this research is secondary data of trading volume stockin Indonesia Stock Exchange on the period from 2016 to 2019. Using SPSS (statistical package for thesocial sciences), methods of analysis used in this study include tolerance and VIF test, Kolmogorov-Smirnov test, multivariate cointegration tests: Test, SRESID and ZPRED estimation, PearsonCorrelation Product Moment, t- statistical tests, F-statistical test, and coefficient of determination (R2).The result of this research show that earning per share (EPS), return on equity (ROE), have significantinfluence on the growth in share transaction volume, but price growth and debt to equity ratio (DER)have no significant influence on the growth in share transaction volume. All the independent variablessimultaneously from a good model to explain the growth in stock transaction volume since themagnitude of the effect value is 99.1%, while 0.9% is explained by other variables besides the growthof stock prices, earnings per share (EPS), return on equity (ROE), and debt to equity ratio. (DER).